KONSEP DIRI PEREMPUAN CANTIK DI INSTAGRAM - Chika Ananda Putri Irza; Ivan Taufiq; Hermanto, Budi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
This article discusses how the self-concept of beautiful women on Instagram by the phenomenon of beauty standards on Instagram. The impact of this image of beauty standards makes women feel insecure, comparing themselves to others on Instagram and losing their motivation. This research method uses a qualitative descriptive with a phenomenological approach. This research uses aspects of self-concept, through Knowledge, Expectations, and Assessment. As A result of this study, nformants use the information on Instagram to be able to add insight. The informants also learned to love themselves and felt much more comfortable and motivated with their current version of themselves. The informants actually learn from previous experiences so that they can continue to improve themselves so that in the future they become better people.